Pelatihan Hypnosis Untuk Meregulasi Stres Dalam Lingkungan Kerja Anggota Sabhara Polda Sulawesi Selatan - Ahmad Razak; Saiid Irham Febrian; Nur Maghfira Nisza; Husniah Husniah; Merna Karlely; Nurul Istiqamah (STKIP Andi Matappa, 2022)
Work stress is a feeling of pressure or a sense of pressure experienced by employees in facing their work. Hypnonsis according to Muhammad Noer is a method of communicating, both verbal and non-verbal, which is persuasive and secresive to a person so that he becomes creative and then reacts according to the basic spiritual value system that a person has. The method of implementation to sabhara members by conducting hypnotherapy training with the theme